2017
DOI: 10.5296/emsd.v6i1.10271
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Knowledge, Attitudes, and Clothing Practices of Turkish Farmers

Abstract: The purpose of this study was to assess Turkish farmers" knowledge, attitudes, and clothing practices during pesticide activities. Seventy male farmers from seven districts of the Aegean region of Turkey were interviewed. Farmers indicated a high level of knowledge of adverse health effects associated with pesticides. In contrast to their level of knowledge, over 50% of the farmers had the attitude that pesticides would not be harmful to them. The type of clothing most often worn further supported the farmers"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
4
3
1
Order By: Relevance
“…[28] The significant relationship found reflects the positive effects of farmers' knowledge and attitudes on the use of personal protective equipment. The results of the Derafshi[29] study among Turkish farmers showed the reverse results compared to this study. In the Derafshi study, the ineffectiveness of farmers' attitudes toward their use of personal protective equipment was reported to be the reason for the lack of significant relationship between knowledge and attitude, and between the knowledge and use of personal protective equipment, and also the negative relationship between attitude and use of personal protective equipment.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…[28] The significant relationship found reflects the positive effects of farmers' knowledge and attitudes on the use of personal protective equipment. The results of the Derafshi[29] study among Turkish farmers showed the reverse results compared to this study. In the Derafshi study, the ineffectiveness of farmers' attitudes toward their use of personal protective equipment was reported to be the reason for the lack of significant relationship between knowledge and attitude, and between the knowledge and use of personal protective equipment, and also the negative relationship between attitude and use of personal protective equipment.…”
Section: Discussioncontrasting
confidence: 86%
“…In the Derafshi study, the ineffectiveness of farmers' attitudes toward their use of personal protective equipment was reported to be the reason for the lack of significant relationship between knowledge and attitude, and between the knowledge and use of personal protective equipment, and also the negative relationship between attitude and use of personal protective equipment. [29]…”
Section: Discussionmentioning
confidence: 99%
“…The results of our survey show that most participants understood pesticides can have harmful effects on the health of applicators and the environment. Turkish farmers also thought that pesticides upset the balance between nature (soil, plants, and animals) and humans [88]. Similar findings have been revealed that in Ethiopia [89], Kuwait [90] and Palestine, farmers were well aware of the relationship between pesticides and health problems, including respiratory problems, while the majority of farmers (87.8%) had no idea about pesticide residues.…”
Section: Discussionsupporting
confidence: 69%
“…Nearly half of the farmers have the practice of showering and washing their clothes separately. Similar results have been found in the study conducted at Turkey [29] and in Iran [30].…”
Section: Safety Practicessupporting
confidence: 90%